1982
DOI: 10.1177/0310057x8201000213
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to both Decamethonium and Suxamethonium

Abstract: Intradermal testing is a reliable method of determining the drug or drugs responsible for an anaphylactic reaction.1 Adequate explanation and documentation given to the patient can be effective in preventing subsequent reactions.2 The case of a patient who had a second lifethreatening reaction despite these precautions is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In five other patients we have investigated who reacted to suxamethonium, five showed positive skin tests to suxamethonium and decamethonium, and originally we concluded that for subject 14 an error had been made on the first skin test. 9 Five years later, intradermal tests and the RIA were positive, and on a subsequent occasion two years later, the intradermal test for suxamethonium was negative while the RIA remained positive.…”
Section: Groupmentioning
confidence: 94%
See 1 more Smart Citation
“…In five other patients we have investigated who reacted to suxamethonium, five showed positive skin tests to suxamethonium and decamethonium, and originally we concluded that for subject 14 an error had been made on the first skin test. 9 Five years later, intradermal tests and the RIA were positive, and on a subsequent occasion two years later, the intradermal test for suxamethonium was negative while the RIA remained positive.…”
Section: Groupmentioning
confidence: 94%
“…One patient (Case 14) who has been described in detail 9 is worthy of individual mention. This patient initially reacted to decamethonium and one month later was skin test positive to decamethonium and skin test negative to suxamethonium, and had IgE serum antibodies to suxamethonium detected by RIA.…”
Section: Groupmentioning
confidence: 99%